Completing the redox-series of silicon trisdioxolene: ortho-quinone and Lewis Superacid make a powerful redox catalyst - Maskey, Rezisha; Bendel, Christoph; Malzacher, Jonas; Greb, Lutz (Chemistry - a European journal, 2020)
Quinones are mild oxidants, the redox potentials of which can be increased by supramolecular interactions. Whereas this goal has been achieved by hydrogen bonding or molecular encapsulation, a Lewis acid-binding strategy for redox amplification of quinones is unexplored. Herein, the redox chemistry of silicon tris(perchloro)dioxolene 1 was studied, which is the formal adduct of ortho-perchloroquinone QCl with the Lewis superacid bis(perchlorocatecholato)silane 2. By isolating the anionic monoradical 1.−, the redox-series of a century-old class of compounds was completed. Cyclic voltammetry measurements revealed that the redox potential in 1 was shifted by more than 1 V into the anodic direction compared to QCl, reaching that of “magic blue” or NO+. It allowed oxidation of challenging substrates such as aromatic hydrocarbons and could be applied as an efficient redox catalyst. Remarkably, this powerful reagent formed in situ by combining the two commercially available precursors SiI4 and QCl.